1999
DOI: 10.1002/(sici)1521-4141(199903)29:03<1051::aid-immu1051>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CD4+ T cells in mouse bone marrow. I. Increased activated/memory phenotype and altered TCR Vβ repertoire

Abstract: A significant proportion of memory B cells home to bone marrow (BM) which is a major site of anamnestic antibody responses in mice. We hypothesized that memory T cells likewise accumulate in BM perhaps to provide help for antibody production, and that the compartment of CD4+ T cells in BM of unimmunized mice would be enriched for memory phenotype cells that might have been activated by environmental antigens. The phenotype of activated/memory CD4+ lymphocytes has been defined as CD44hi CD45RBlo CD62L-. Convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 16 publications
7
30
0
Order By: Relevance
“…Previous papers reported an unusual activation phenotype in BM T cells. [23][24][25] In line with these descriptions, we found that in normal BALB/c mice, CD4 ϩ BM T-cell populations are enriched with activated T cells as assessed by CD62L and CD45RB expression ( Figure 5A). These cells show a predominantly activated/memory phenotype (CD62L low CD45RB int/low ), indicating a previous antigenic stimulation.…”
Section: Bone Marrow T Cells Are Activated In Normal Micesupporting
confidence: 78%
See 1 more Smart Citation
“…Previous papers reported an unusual activation phenotype in BM T cells. [23][24][25] In line with these descriptions, we found that in normal BALB/c mice, CD4 ϩ BM T-cell populations are enriched with activated T cells as assessed by CD62L and CD45RB expression ( Figure 5A). These cells show a predominantly activated/memory phenotype (CD62L low CD45RB int/low ), indicating a previous antigenic stimulation.…”
Section: Bone Marrow T Cells Are Activated In Normal Micesupporting
confidence: 78%
“…Bone marrow T cells make up only 1% to 3% of BM microenvironment and have activated phenotype and semidiverse V␤ repertoire. [23][24][25] Moreover, it is still unclear if activation takes place in the periphery, in the bone marrow, or in both. Interestingly enough, in common gamma chain-deficient mice (␥ c Ϫ/Ϫ ) a deregulated activated CD4 ϩ T-cell population enhances BM hematopoiesis and promotes the appearance of extramedullary hematopoietic foci.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, since to help hematopoiesis T cells must be activated, we looked at the activation status of these cells in the bone marrow of normal mice. In agreement with previous descriptions (17,19) we found an increased proportion of activated CD4 + T cells in mouse bone marrow -most of them showing an early activated phenotype (5).…”
Section: Introducing the Recent Findingssupporting
confidence: 93%
“…We and others have found an increased number of activated T cells in mouse bone marrow (5,17,19,20). This is true for both CD4 + and CD8 + T cells.…”
Section: The Second Problem: How Bone Marrow T Cells Become Antigenprsupporting
confidence: 57%
See 1 more Smart Citation